Rhabdomyolysis Occurred Again after Changing Chemotherapy Regimens in Ovarian Cancer: A Case Report - Shaocong Cao; Tao Peng (Case Reports in Oncology)
Introduction: The incidence of chemotherapy-induced rhabdomyolysis is rare, but it is a syndrome that may cause death and should be paid attention to clinically. Case Presentation: Here, we report a case of rhabdomyolysis in an ovarian cancer patient after chemotherapy. After the symptoms were relieved, the chemotherapy regimen was changed, and rhabdomyolysis occurred again. Conclusion: The occurrence of rhabdomyolysis is mainly caused by certain specific chemotherapy drugs such as gemcitabine and paclitaxel and is not closely related to other factors such as the patient’s constitution or genetic factors. And the occurrence of rhabdomyolysis can be caused by conventional doses of drugs rather than high dose. If rhabdomyolysis occurs and is completely relieved, chemotherapy may be considered again depending on the patient’s condition and physical condition. However, caution should be exercised in selecting drugs to avoid recurrence of rhabdomyolysis, and the condition should be closely monitored.